The Legitimacy of Classical Dance Gagrag Ngayogyakarta - Hadi, Y. Sumandiyo (PANGGUNG, 2017)
ABSTRACT This article of research findings is to reveal the existence of classical dance style of Yogyakarta, since the government of Sultan Hamengku Buwono I, which began in 1756 lasted up until now on era government of Sultan Hamengku Buwono X. The legitimation of classical dance is considered as "gagrag Ngayogyakarta", furthermore not only preserved in the palace, but living and growing, and may be examined by general public. The dance was first considered as a source of classical dance âgagrag Ngayogyakartaâ, created by Sultan Hamengku Buwono I, ie Beksan Lawung Gagah, or Beksan Trunajaya, Wayang Wong or dance drama, and Bedaya dance. Three dances until now can be categorized as a sacred dance, to review performances that are related to traditional ceremonies, or rituals. Three types of dance later developed other types of classical dance âgagrag Ngayogyakartaâ, which is categorized as a kind of secular dance for entertainment performance.Keyword: Sultan Hamengku Buwono, classical dance âgagragâ or style of Yogyakarta, legitimacy, sacred or ritual dance, secular dance